Medical Students Have Limited Awareness, Knowledge, Beliefs, and Experiences of Pre-exposure Prophylaxis (PrEP) for HIV Prevention. (4th October 2017) - Imp, Brandon; Allen, Elaine; Volk, Jonathan; Bhowmick, Tanaya
Abstract: Background: While studies of healthcare professionals have shown increasing awareness, knowledge, positive beliefs, and prescribing practices of emtricitabine/tenofovir pre-exposure prophylaxis (PrEP) for HIV prevention, PrEP is still underutilized in clinical practice. PrEP knowledge is associated with increased prescription so early education of healthcare professionals is recommended, but the extent of PrEP education in medical school is unknown. In this analysis, we describe medical students' awareness, knowledge, beliefs, and experiences regarding PrEP. Methods: Medical students at 18 US allopathic medical schools completed a survey on knowledge, beliefs, and experiences of PrEP in May–June 2016. Knowledge was assessed with a 10-question quiz on PrEP facts. No incentives to complete the survey were offered. Data were summarized by frequency (%) for categorical variables and with means (SD) for continuous variables. Chi-squared tests were used to examine differences between knowledge of PREP and other categorical variables. Results: The study population ( N  = 1588) included women (53%), non-Caucasians (27%), and non-heterosexuals (15%). Median age was 25 (range 21–53). Forty-eight home states, including D.C., and 21 home countries were represented. 18% of fourth-year students were never taught about PrEP in medical school, compared with 40% of first-year students ( P  < 0.001). Overall, 28% of students were unaware of PrEP. Those unaware believed patients without HIV will not adhere to PrEP ( P  < 0.001). Awareness was associated with knowing someone with HIV besides a patient and experience caring for HIV-infected, intravenous drug-using, and LGBTQ people ( P  < 0.001). Higher knowledge scores were associated with confidence in determining a patient's candidacy for PrEP and, for third- and fourth-year students, having recommended PrEP in the clinical setting ( P  < 0.001). Overally, 57% believed that behavioral intervention should be tried before prescribing PrEP, 45% believed that patients would not adhere to PrEP, and 22% worried that PrEP is not effective. Conclusion: We show in an 18-site study that medical students have limited awareness, knowledge, positive beliefs, and experiences of PrEP. Given these findings and the underutilization of PrEP by current practitioners, we recommend increasing the inclusion of PrEP in medical student education. Disclosures: All authors: No reported disclosures.